Effect of Thermal Annealing Temperatures on MSM Photo Detector Based on Ge-like Micro Flowers in the Dark Mode - M.J. Jawad; Haider Y. Hammod; Amer B. Dheyab (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In this research , a current density of J = 7.5 mA/cm2 was applied over a constant duration of 2 h to grow Ge-like microflowers on Si. To fabricate a photodetector, Pd was deposited by RF-sputtering as metal contact with Ge. The samples were subjected to rapid thermal annealing (RTA) in ambient N2 at 100,200° and 300°C for 10 min. By screening the samples from electrical noise, the electrical characteristics through current-voltage measurements were carried out at room temperature before and after annealing. The measurements were performed in the dark, white light and UV illuminations. The forward I-V characteristics were analyzed using standard thermionic emission relation for electron transport from Metal-semiconductor-metal(MSM)with low doping concentration .The saturation current was obtained as the intercept from the straight line of ln I versus V, T. It was found that at 5V, these currents were 2.45 × 10-5, 5.77× 10-5, 6.12× 10-4 A, respectively. Also characteristics of the MSM photodetector, linear and logarithmic forward and reverse bias, at different annealing temperatures: as-deposited, 100°C, 200°C and 300°C in the dark mode.